2020
DOI: 10.1111/bjh.16752
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of serum B‐cell maturation antigen levels predicts overall survival among multiple myeloma patients starting treatment

Abstract: Serum B-cell maturation antigen (sBCMA) is a novel biomarker for B-cell malignancies. A normal reference range (<82Á59 ng/ml) has been recently established but the impact of achieving normal levels to outcomes for patients receiving treatment for B-cell malignancies has not been studied. We first found that among multiple myeloma (MM) patients starting a new treatment, those who begin treatment within normal sBCMA limits (<82Á59 ng/ml) have improved progression-free survival (PFS; P = 0Á0398) and overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
4
13
0
2
Order By: Relevance
“…This study reinforces the value of sBCMA as a prognostic biomarker for PFS among MM patients 14 . Specifically, those with elevated sBCMA consistently show shorter PFS regardless of the type of treatment that the patient is receiving 14,18 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study reinforces the value of sBCMA as a prognostic biomarker for PFS among MM patients 14 . Specifically, those with elevated sBCMA consistently show shorter PFS regardless of the type of treatment that the patient is receiving 14,18 .…”
Section: Discussionsupporting
confidence: 81%
“…We have recently shown that changes in sBCMA levels predict PFS regardless of the drugs which the patient is receiving. 14 Having a serum marker, that is, unrelated to the monoclonal antibody produced by the malignant clone provides another way to assess changes in clinical status and help avoid the limitations of using only antibody-related biomarkers to assess changes in the clinical status of MM patients. This new biomarker will also provide the treating healthcare professional with more reassurance that the changes in clinical status as determined with this marker are truly reflective of the patient's current clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…В результате действия γсекретаз мембранная форма BCMA расщепляется, что приводит к образованию растворимой формы BCMA (sBCMA) [25]. Определение данной молекулы в сыворотке крови, как оказалось, имеет важное зна чение, в частности для прогностической оценки эф фективности BCMAнаправленной терапии [26].…”
Section: в качестве новой стратегии лечения мм помимо ставших уже привычными моноклональных антител против Cd38 и Slamf7 рассматривается unclassified
“…Patients with levels above the median had shorter progression free survival and overall survival ( 140 ). Normalization of sBCMA during any treatment was predictor of increased overall response rate, overall survival ( 141 ), and achievement of complete response ( 141 ). Currently, sBCMA ( 139 , 140 ) and sTACI are investigated as novel biomarker of disease activity in B-cell disorders with prognostic value ( 142 ), with two main advantages: independence from renal kidney and shorter half-life (24–36 h) than monoclonal components IgG (21 days) and IgA (7 days), or free light chains ( 140 , 141 ).…”
Section: The Baff-april-bcma Systemmentioning
confidence: 99%